Downregulation of MHC Class I Expression by Influenza A and B Viruses - Koutsakos, Marios; McWilliam, Hamish E. G.; Aktepe, Turgut E.; Fritzlar, Svenja; Illing, Patricia T.; Mifsud, Nicole A.; Purcell, Anthony W.; Rockman, Steve; Reading, Patrick C.; Vivian, Julian P.; Rossjohn, Jamie; Brooks, Andrew G.; et al. (Frontiers in Immunology, 2019)
Manipulation of the MHC-I presentation pathway, and thus limiting MHC-I cell surface expression, is used by many viruses to evade immune recognition. In particular, downregulation of MHC-I molecules at the cell surface can reduce the ability of CD8+ T cells to recognise viral peptides presented by MHC-I molecules and thereby delay viral clearance by CD8+ T cells. To date, MHC-I downregulation by influenza viruses has not been reported. Given that influenza virus infections are a global health concern and that CD8+ T cells play an important role in promoting influenza virus clearance and recovery from influenza disease, we investigated whether influenza A and B viruses (IAV, IBV) downregulated MHC-I as a novel mechanism to evade cellular immunity. Here, we showed that infection of several cell types, including epithelial A549 cells, with a panel of IAV and IBV viruses downregulated the surface MHC-I expression on IAV/IBV-infected cells during the late stages of influenza virus infection. This observation was consistent across a panel of class I-reduced (C1R) cell lines expressing 14 different HLA-A or -B alleles and a panel of 721.221 cell lines expressing 11 HLA-C alleles. Interestingly, IBV infection caused more pronounced reduction in surface MHC-I expression compared to IAV. Importantly, the two viruses utilized two distinct mechanisms for MHC-I downregulation. Our data demonstrated that while IAV caused a global loss of MHC-I within influenza-infected cells, IBV infection resulted in the preferential loss of MHC-I molecules from the cell surface, consequent of delayed MHC-I trafficking to the cell surface, resulting from retaining MHC-I intracellularly during IBV infection. Overall, our study suggests that influenza viruses across both IAV and IBV subtypes have the potential to downregulate MHC-I surface expression levels. Our findings provide new insights into the host-pathogen interaction of influenza A and B viruses and inform the design of novel vaccine strategies against influenza viruses.